Investigation of Microstructure and Mechanical Properties of Aluminium 5356 Using Wire Arc Additive Manufacturing - K.Saravanakumar; S.Ananth; J.Medoline; M.Dharshini; K.M.Sansuuki Priyanka (Journal of Advanced Mechanical Sciences)
Wire arc additive manufacturing is a 3D metal printing method that constructs objects layer by layer using an electric arc. In this study, a base of Aluminum 6082 alloy is used to create a multi-layer structure. An automatic gas metal arc welding process is employed, with parameters such as current, stick-out distance, and travel speed. To facilitate the gas metal arc welding (GMAW) process, Aluminum 5356 is utilized as filler material. Three factor and three level approach was taken for the L9 design of experiments to build multiwall structure. Pure Argon serves as the inert gas in this experiment. The L9 experiment led to the selection of the optimal process parameters. The zig-zag tool path strategy is employed to disperse residual stress and prevent lengthy, continuous weld lines. The liquid penetrant test reveals that samples one to four are rejected due to overfill. Samples seven and eight exhibit reduced joint and fatigue strength due to a smaller bead width. The sixth weld bead sample is chosen as the ideal process parameter, showing minimal undercuts and reduced overfills compared to other samples. This research demonstrates the potential of WAAM for creating high-quality multi-layer structures while optimizing process parameters for superior outcomes